2020
DOI: 10.1088/2053-1591/ab66ed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regular and core shell nano fillers on the partial discharge and tracking performance of low density polyethylene

Abstract: Solid insulation materials are the backbone for all kinds of outdoor insulation applications. Environmental stresses degrade every outdoor insulation material with the passage of time. Internal partial discharges and external surface tracking are the two major factors governing the health of outdoor insulation. Best outdoor insulation is the one having lowest level of partial discharge and highest resistance to tracking. Improvement in tracking resistance of polymeric insulation materials has been a concern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Again, the nanofillers serve as a barrier on the surface sample against PD attack. These findings were supported by Awan et al [ 30 ] and Chandrasekar et al [ 31 ] who confirmed that the addition of nanofillers could enhance the ability of XLPE nanocomposites to withstand surface degradation due to PD. The trend of PD characteristics for PDIV, PDEV, PD magnitudes, and PD numbers have showed the same trend, which indicated that the most effective formulation was sample 0.8 wt.%, followed by sample 1.0 wt.%, and sample 0.5 wt.%.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Again, the nanofillers serve as a barrier on the surface sample against PD attack. These findings were supported by Awan et al [ 30 ] and Chandrasekar et al [ 31 ] who confirmed that the addition of nanofillers could enhance the ability of XLPE nanocomposites to withstand surface degradation due to PD. The trend of PD characteristics for PDIV, PDEV, PD magnitudes, and PD numbers have showed the same trend, which indicated that the most effective formulation was sample 0.8 wt.%, followed by sample 1.0 wt.%, and sample 0.5 wt.%.…”
Section: Resultssupporting
confidence: 64%
“…The nanofillers serve as a barrier on the surface sample against PD attack. An indication supported by [ 30 ] confirmed that the addition of nanofillers enhanced the ability of XLPE nanocomposites to withstand surface degradation due to PD. Furthermore, the PRPD results show that the occurrences of PD pulses at 0.8 wt.% is the optimum amount of LDH-Al 2 O 3 nanoparticles to incorporate in the XLPE matrix.…”
Section: Resultsmentioning
confidence: 76%
“…The dielectric properties and space charge behavior of epoxy resin/nanocomposites with nano-fillers SiO 2 and Al 2 O 3 ions [13,14]. The effect of epoxy species on the tensile and electrical insulation properties of epoxy/ micro-silica composites using three species of epoxy resins for high-voltage insulators was investigated in [15]. Polymer nanocomposites are used in power capacitors for electrical energy storage [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of NCs depend on several parameters, for instance, matrix material, nanophase dimension, size, shape, orientation, and dispersion [6]. Additionally, the distinctive blend of matrix elements, including polymer, carbon, metal, ceramics, and other types of reinforcements, such as fibers, particles, and layered materials, has been widely used for the creation of composites [7]. A class of nanomaterials called polymer nanocomposites is made up of many solid phases.…”
Section: Introductionmentioning
confidence: 99%